2019
DOI: 10.1038/s41598-019-40619-1
|View full text |Cite
|
Sign up to set email alerts
|

The NLRP3 inflammasome modulates glycolysis by increasing PFKFB3 in an IL-1β-dependent manner in macrophages

Abstract: Inflammation and metabolism are intricately linked during inflammatory diseases in which activation of the nucleotide-binding domain–like receptors Family Pyrin Domain Containing 3 (NLRP3) inflammasome, an innate immune sensor, is critical. Several factors can activate the NLRP3 inflammasome, but the nature of the link between NLRP3 inflammasome activation and metabolism remains to be thoroughly explored. This study investigates whether the small molecule inhibitor of the NLRP3 inflammasome, MCC950, modulates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
97
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 20 publications
3
97
0
Order By: Relevance
“…We identified aberrant responses following exposure to classical pro‐inflammatory stimuli (LPS/IFNγ) in TREM2 hypomorphic iPS‐Mg; specifically, reduced morphological changes and TNFα release. Both responses require rapid energy production which is produced when microglia undergo the metabolic switch to glycolysis . Glycolysis allows energy production and uptake of essential nutrients to support the rapid changes required by “activated” microglia in response to a stimulus, such as phagocytosis, proliferation, migration, and induction of protein synthesis for cytokine and chemokine secretion .…”
Section: Discussionmentioning
confidence: 99%
“…We identified aberrant responses following exposure to classical pro‐inflammatory stimuli (LPS/IFNγ) in TREM2 hypomorphic iPS‐Mg; specifically, reduced morphological changes and TNFα release. Both responses require rapid energy production which is produced when microglia undergo the metabolic switch to glycolysis . Glycolysis allows energy production and uptake of essential nutrients to support the rapid changes required by “activated” microglia in response to a stimulus, such as phagocytosis, proliferation, migration, and induction of protein synthesis for cytokine and chemokine secretion .…”
Section: Discussionmentioning
confidence: 99%
“…33 Furthermore, we have found that the classical substrates of caspase-1, that is, IL-1β and IL-18, were strongly reduced in CSE-treated macrophages. 46,49 As an adaptive response during infection, activation of caspase-1 reduces the cellular glycolytic rate by promoting the cleavage of glycolytic enzymes. Optimal activation of macrophages is sustained by the increase of the glycolytic flux that generates, among others, a positive crosstalk between glycolysis and the NLRP3 inflammasome that is required for proper response to infections.…”
Section: Discussionmentioning
confidence: 99%
“…Further, studies proved that NLRP3 inflammasome is predominantly activated in macrophages and up‐regulated in M1 macrophages but down‐regulated in M2 . What is more, the inhibition of NLRP3 impeded glycolysis and induced a macrophage phenotype transformation from pro‐inflammatory to anti‐inflammatory . Therefore, we investigated the effect of AOAA on NLRP3‐Caspase1/IL‐1β signalling pathway by Western blotting and qPCR analysis.…”
Section: Resultsmentioning
confidence: 97%